Antibacterial, Anti-Inflammatory, Antioxidant, and Antiproliferative Properties of Essential Oils from Hairy and Normal Roots of Leonurus sibiricus L. and Their Chemical Composition. (16th January 2017) - Sitarek, Przemysław; Rijo, Patricia; Garcia, Catarina; Skała, Ewa; Kalemba, Danuta; Białas, Adam J.; Szemraj, Janusz; Pytel, Dariusz; Toma, Monika; Wysokińska, Halina; Śliwiński, Tomasz
Abstract : Essential oils obtained from the NR (normal roots) and HR (hairy roots) of the medicinal plant Leonurus sibiricus root were used in this study. The essential oil compositions were detected by GC-MS. Eighty-five components were identified in total. Seventy components were identified for NR essential oil. The major constituents in NR essential oil were β -selinene (9.9%), selina-4, 7-diene (9.7%), (E) - β -caryophyllene (7.3%), myli-4(15)-ene (6.4%), and guaia-1(10), 11-diene (5.9%). Sixty-seven components were identified in HR essential oil, the main constituents being (E) - β -caryophyllene (22.6%), and germacrene D (19.8%). The essential oils were tested for cytotoxic effect, antimicrobial, anti-inflammatory, and antioxidant activities. Both essential oils showed activity against grade IV glioma cell lines (IC50 = 400  μ g/mL), antimicrobial (MIC and MFC values of 2500 to 125  μ g/mL), and anti-inflammatory (decreased level of IL-1 β, IL-6, TNF- α, and IFN- γ in LPS-stimulated cells).The essential oils exhibited moderate antioxidant activity in ABTS (EC50 = 98 and 88  μ g/mL) assay. This is the first study to examine composition of the essential oils and their antimicrobial, antioxidant, antiproliferative, and anti-inflammatory activities. The results indicate that essential oils form L. sibiricus root may be used in future as an alternative to synthetic antimicrobial agents with potential application in the food and pharmaceutical industries.